PEMBATALAN PESANAN DI PT GO-JEK DALAM PERSPEKTIF KOMPILASI HUKUM EKONOMI SYARIAH (KHES) - Salsabilla, Naya Atiqa; Syahbudi, Syahbudi; Anggriana, Anggita (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2024)
This study aims to determine the factors that cause cancellation of orders between drivers and consumers on the Go-Jek application. Knowing the KHES view on canceling orders between drivers and consumers on the Go-Jek application. The research uses qualitative research methods with the type of field research and normative sociological approach. Data collection techniques used by researchers are observation methods, interviews with sources and documentation. Data analysis researchers do data reduction, data display, and conclusion drawing. Then the data is checked for validity by tringulation of sources. The argument of this research is that the implementation of order cancellation both by consumers and drivers is influenced by legal awareness that is paragmatic, but accommodates the wishes of the parties. This research provides an understanding of several factors that cause the cancellation of orders between drivers and consumers in the Go-Jek application including: 1. From the consumer's point of view: long pick-up time due to weather or vehicle problems, Driver's identity does not match the application, the vehicle number does not match the Driver's account. 2. From the Driver's point of view: the order is too far above 4 km so the cost of gasoline is high, there is a problem with the vehicle. According to KHES, the relationship between consumers and Gojek drivers can be seen as an Ijarah contract. However, KHES prohibits unilateral cancellation unless there are legally justified reasons.